Happy narwhalidays : Narwhal and Jelly # 5 - Clanton, Ben, 1988- (New York : Tundra, 2020)
Narwhal and Jellyfish gear up for the Christmas and holiday season. It is sure to be full of kindness, imagination, and waffles.
new kid book 2022 fall.
Publishers Weekly, 09/21/2020.
Kirkus Review, 09/01/2020.
1-4.
Keywords: Holidays -- Fiction; Jellyfishes -- Fiction; Narwhal -- Fiction; Humorous fiction